The Role and Effectiveness of the Ciletuh-Palabuhanratu Geopark in Acceleration Achievement of Sustainable Development Goals Pillars of Economic Development - Uswatun Khasanah; Dwi Nowo Martono; Supriatna Supriatna (Postgraduate, University of Mataram, 2023)
Geoparks are developed areas for sustainable development, both from social, economic, and environmental aspects. The Ciletuh-Palabuhanratu Geopark, Sukabumi Regency, West Java Province, which has been recognized as a UNESCO Global Geopark, is believed to be able to contribute to building the local community's economy with the geotourism activities it offers. It is hoped that improving the local economy will help improve the quality and welfare of people's lives. It will accelerate the achievement of SDGs targets in the pillars of economic development, especially SDGs 8. This research aims to analyze the role and effectiveness of the Ciletuh-Palabuhanratu Geopark as an agent for accelerating the achievement of SDG 8. The method used is a combined method, statistical descriptive and qualitative with structured interviews with business actors and tourism community members. The research results show that three indicators have been achieved: increasing the number of tourists, workers, and industrial linkages, but sub-indicators in industrial linkages, namely restaurants and travel services, have yet to be maximized. In general, the Geopark has been proven to function as a means of contributing to the achievement of SDG 8. Still, it requires particular strategies to increase growth in economic sub-indicators to achieve the SDG 8.